2014
DOI: 10.1186/gm535
|View full text |Cite
|
Sign up to set email alerts
|

Identification of somatic mutations in EGFR/KRAS/ALK-negative lung adenocarcinoma in never-smokers

Abstract: BackgroundLung adenocarcinoma is a highly heterogeneous disease with various etiologies, prognoses, and responses to therapy. Although genome-scale characterization of lung adenocarcinoma has been performed, a comprehensive somatic mutation analysis of EGFR/KRAS/ALK-negative lung adenocarcinoma in never-smokers has not been conducted.MethodsWe analyzed whole exome sequencing data from 16 EGFR/KRAS/ALK-negative lung adenocarcinomas and additional 54 tumors in two expansion cohort sets. Candidate loci were valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…Recurrent mutations in CDH10 have recently been reported in EGFR/KRAS/ALK mutation-negative lung adenocarcinoma in never-smokers [25] and as a prognostic mutation signature in colorectal cancer [26]. Our study indicated that CDH10 is not only the most commonly and significantly mutated gene in SCLC but also associated with poor survival in SCLC.…”
Section: Discussionsupporting
confidence: 63%
“…Recurrent mutations in CDH10 have recently been reported in EGFR/KRAS/ALK mutation-negative lung adenocarcinoma in never-smokers [25] and as a prognostic mutation signature in colorectal cancer [26]. Our study indicated that CDH10 is not only the most commonly and significantly mutated gene in SCLC but also associated with poor survival in SCLC.…”
Section: Discussionsupporting
confidence: 63%
“…It has been found to be mutated in lung adenocarcinoma negative for mutations in EGFR/KRAS/ALK [31]. …”
Section: Resultsmentioning
confidence: 99%
“…Other genes with deleterious mutations in ≥3 primary tumors were MLL3, SETD2, ATM, ARID1A, CRIPAK, FAM135B, HGF, AR, BAI3, EP300, KDR, PAPPA2, PDGRRA and RUNX1 . Several of those genes, such as ATM [7], MLL3 [42], and SETD2 [6,43], were recently reported to be frequently mutated/changed in lung cancers, suggesting that their mutations may be used as biomarkers for these cancers. A number of large genes included in the analysis, such as CSDM3, CSDM1, HYDIN , LRP2, LRP1B, PCLO, and RYR2, most of them encoding proteins with >4000 amino acids, were also found to have high mutation frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…Whether those EGFR mutations contribute to tumorigenesis or sensitize cancers to anti-EGFR therapy remains to be determined. Several genes, such as ATM [7], MLL3 [42], and SETD2 [6,43], were recently reported to be frequently mutated/changed in lung cancers. In addition, several large genes that were included in the analysis, such as CSDM3, CSDM1, HYDIN , LRP2, LRP1B, PCLO, and RYR2, were also found to be frequently mutated in our lung cancer samples.…”
Section: Discussionmentioning
confidence: 99%